Mitigating Large Vibrations of Stayed Cables in Wind and Rain Hazards - Hung Vo-Duy; Cung H. Nguyen (Shock and Vibration)
This paper presents an experimental investigation of stayed cable vibrations in dry-wind and rain-wind coupling hazards. To mitigate large vibrations of the cable, the use of spiral wires wrapped around the cable is proposed. By testing two cable models in a wind tunnel in dry and rain conditions for different yaw angles and wind speeds, the effectiveness of using the spiral wires to mitigate large vibrations is clarified. Finally, the paper provides a further understanding of the complex mechanism of wind-induced and rain-wind-induced vibrations. It is found that the low-frequency vortex flows in the wake play a significant role in the excitation of large responses of the cable in high wind speeds. The spiral wires dismiss these low-frequency flows and then reduce the large vibrations.